How do you simplify (8y^3)(-3x^2y^2)(3/8xy^4)(8y3)(3x2y2)(38xy4)?

2 Answers
Jan 10, 2018

-9x^3y^99x3y9

Explanation:

Well, since multiplication is commutative we can change the order and group similar variables together and constants together, so this is same as
(8)(-3)(3/8)(y^3y^2y^4)(x^2x)(8)(3)(38)(y3y2y4)(x2x)
Then we can cancel 8/888 since = 1=1 and left with (-3)(3)=-9(3)(3)=9 for constant part. When multiplying powers with same base we add exponents so (y^3y^2y^4)=y^9(y3y2y4)=y9
And (x^2x)=x^3(x2x)=x3.

Putting it all back together gives -9x^3y^99x3y9

Jan 10, 2018

color(blue)(-9x^3y^9)9x3y9

Explanation:

Multiply it out:
(8y^3)(-3x^2y^2)(3/8xy^4)(8y3)(3x2y2)(38xy4)
When multiplying variables, add the exponents:
(-24x^2y^5)(3/8xy^4)(24x2y5)(38xy4)
color(blue)(-9x^3y^9)9x3y9